RESILIENCE OF HONORARY TEACHERS AND ITS IMPLICATIONS FOR THE PROCESS TEACHER LEARNING AT MTs IN SIBULUE DISTRICT BONE REGENCY - Adriani Adriani; Ali Halidin; Khaeruddin Kiramang (Education Studies and Teaching Journal (EDUTECH), 2025)
This study aims to examine the resilience of honorary teachers and its implications for the learning process at Madrasah Tsanawiyah (MTs) in Sibulue District, Bone Regency. This study uses a descriptive analytical approach with a field research type (field research), through interviews, observations, and documentation in several private MTs: MTs Ibadurrahman Mutttahida, MTs Ar-Rahman Kaju, MTs Yapis Pattiro Bajo, MTs Al-Zaky Pattiro Sompe, and MTs Al-Mubarak.The results of the study show that the resilience of honorary teachers is not only reflected in Grotberg's theory (I Am, I Have, I Can), but also strengthened by Islamic values, namely patience, gratitude, trust, brotherhood, sincerity, and mujahadah an-nafs.The challenges they face include diverse student characteristics, administrative and technological demands, limited physical and logistical resources, and financial constraints. However, this resilience has had a positive impact on the quality of learning, as evidenced by the design of Lesson Implementation Plans (RPPs), creative use of media, varied teaching methods, development of extracurricular activities, and implementation of student assessments.This study concluded that the greater the challenges faced, the stronger the resilience of honorary teachers, aligning with Islamic teachings that life's trials strengthen faith. Thus, honorary teachers are able to demonstrate professionalism, commitment, and consistency in carrying out their duties.